The effects of horizontal and vertical forces on single scull boat orientation while rowing - Sinclair, P.; Greene, A.; Smith, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Forces produced at the oarlock pins and the foot stretcher, and the orientations of a single scull rowing boat, were investigated in eleven male rowers. Rowers were tested at 32 strokes•minute-1 on an instrumented single scull boat. The pitch of the boat was shown to be increased by the vertical forces applied to the pin and the foot stretcher, and roll was increased by an imbalance of vertical forces delivered to the bow and stroke side pins. Pitch and roll were largest in the late recovery and early drive phase when forces applied to the boat were greatest. It is suggested that the provision of feedback on boat orientation and force production may enable rowers to be trained to reduce changes in orientation and therefore to reduce energy loss through hydrodynamic drag.